Analisa Perbandingan Kuat Sinyal 4G LTE Antara Operator Telkomsel dan XL AXIATA Berdasarkan Paramater Drive Test Menggunakan Software G-NetTrack Pro Di Area Jalan Protokol Panam. - Rendi Efriyendro; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Improved quality of Long Term Evolution (LTE) network can be do it by analyze the performance and coverage each of operator in Indonesia. Signal strength among of telecomunication operator was not in the same performance and individual location. Parameter that determining signal strenght and quality of each service provider is known by RSRP (Reference Signal Receives Power), RSRQ (Reference Signal Receives Quality), SNR (Signal Noice Ratio), and QoS (Quality of Service). A method to gather series of radio network frequency information in the field is used for analyze and measurement of data signal strength is drive test using G-Net TrackPro software. Location of the measurement are located across panam main street, such as HR.Soebrantas, Soekarno-Hatta, Tuanku Tambusai, SM.Amin, and Air hitam - Kubang Raya. The result shows that XL-AXIATA have the strongest signal on panam with -56dbm, followed by telkosel with -62 dbm. The best 4G LTE strenght is on SM Amin street and the worst is on Air Hitam street.Key words: LTE, drive test, RSRP, RSRQ, SNR, QoS, G-Net Track Pro